Nahdlatul Ulama (NU) and the Fiqh of Civilization (Fikih Peradaban): Strategies, Contributions, and Challenges in Overcoming the Humanitarian Crisis - Firmanda Taufiq; Ahalla Tsauro (International Journal Ihya' 'Ulum al-Din, 2024)
Islamic boarding schools (pesantren) as places where Islamic scientific discourse is studied and discussed have become important actors in the study of fiqh. This study has also become one of the things that is often discussed and debated in Islam because fiqh is dynamic compared to other studies. Meanwhile, Nahdlatul Ulama (NU) as one of the largest Islamic mass organizations in Indonesia also has a breakthrough in matters of fiqh, namely proposing civilizational fiqh (fikih peradaban) in response to various global problems. In this case, civilizational fiqh also seeks to find solutions to overcome humanitarian crisis problems, especially those related to conflict and its impacts. This article attempts to show the strategic patterns, contributions, and challenges of Nahdlatul Ulama (NU) in viewing and studying civilizational fiqh in the context of a humanitarian crisis. The theory used in this research is the theory of religious authority. This research is based on library research by examining various relevant literature, both in the form of books, journal articles, research reports, and other related sources needed in this research. Next, the data obtained was analyzed by interpreting the sources obtained and narrated in descriptive form. The results of this research show that Nahdlatul Ulama (NU) has made an important contribution to reforming civilizational fiqh in Indonesia. Apart from that, fiqh can answer various problems of religious practice in society, such as the humanitarian crisis in the world like Palestine-Israel conflict, Rohingya refugees, and many others conflict cases that mediated by NU.